Langerhans Cells: the 'Yin and Yang' of HIV Restriction and Transmission. Issue 3 (March 2017) - Mayr, Luzia; Su, Bin; Moog, Christiane
Abstract : Langerhans cells are specialized sentinels present in the epidermis expressing Langerin, a specific C-type lectin receptor involved in HIV capture and destruction. Recently, the specific mechanism leading to this HIV restriction was discovered. Nevertheless, Langerhans cells can be infected and the way HIV escapes this restriction needs to be unraveled.